The effect of public investment in Europe: A model-based assessment - Jasper de Jong; Marien Ferdinandusse; Josip Funda; Igor Vetlov (European Central Bank (ECB), 2017)
We consider the effect of an increase in public investments on output in Europe against the background of a sharp drop of public investments in a number of EU countries during the crisis and subsequent policy discussions on the need to stimulate public investments. We start with a brief overview of recent developments in public investments, including some methodological issues, and provide a literature overview of the effect of public investments on growth. On the basis of updated estimates of the public capital stock, we estimate the output response to a public capital impulse, using VAR models. In addition, using a structural model, we investigate the sensitivity of the macroeconomic impact of an increase in public investments to alternative assumptions about economic structures and policy implementations.
Keywords: E32; E62; C30; 330; fiscal policy; public investment; euro area; general equilibrium modelling